Răspunsuri

2014-04-17T00:35:03+03:00
Rationalizeaza cu 3√2-4 si o sa iti dea 3√2-4/9*2-16= 3√2-4/2
Cel mai inteligent răspuns!
2014-04-17T00:39:08+03:00
 \frac{1}{3 \sqrt{2} +4} - ( \frac{1}{\sqrt{2}}- \frac{1}{2})* \frac{ \sqrt{18} }{ \sqrt{2}-1 } +3= \\ =   \frac{1}{3 \sqrt{2} +4} -  \frac{  \sqrt{2}-1  }{2}* \frac{3 \sqrt{2} }{\sqrt{2}-1 } +3  \\ =\frac{1}{3 \sqrt{2} +4} -  \frac{3 \sqrt{2}}{2}+3  \\ = \frac{ 3\sqrt{2}-4 }{18-16} -  \frac{3 \sqrt{2}}{2}+3 \\ =\frac{ 3\sqrt{2}-4 }{2} -  \frac{3 \sqrt{2}}{2}+3 \\ = \frac{3 \sqrt{2}-4-3 \sqrt{2} }{2}+3 \\ = \frac{-4}{2}+3 \\ =-2+3=1

:)) să mă uit..
ok .. multumesc
de unde vine pe al doilea rand radical din2 - 1 supra 2 ? "D
:D
1/√2=√2/2